Development of a Knowledge-Based System for Power Electronics Design - Bouketir, Omrane (2005)
Various simulation packages are being widely used to design and simulate electrical and electronic circuits. These simulators require the user to be proficient in designing the circuits and need deep training to be familiar with. Moreover, the design is based on trial and error, till the user reaches the required outputs. Despite their long use, the existing general-purpose simulation packages are still time-consuming when they are used to design power converters especially for inexperienced designers. This is because of the ad-hoc nature of the design task. An approach to overcome the drawbacks of these packages and augment their functionality is to incorporate knowledge-based techniques along with these packages.